2006
DOI: 10.1088/0953-8984/18/41/017
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen storage capacity of titanium met-cars

Abstract: The adsorption of hydrogen molecules on the titanium metallocarbohedryne (met-car) cluster has been investigated by using the first-principles plane wave method. We have found that, while a single Ti atom at the corner can bind up to three hydrogen molecules, a single Ti atom on the surface of the cluster can bind only one hydrogen molecule. Accordingly, a Ti 8 C 12 met-car can bind up to 16 H 2 molecules and hence can be considered as a high-capacity hydrogen storage medium. Strong interaction between two met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…Much work has focused on carbon-based materials such as nanotubes, [4][5][6][7][8][9][10][11][12][13][14] C 60 , 15,16 metal hydrides, and metal-organic frameworks, 17,18 titanium metallocarbohedryne, 19,20 and polyacethylene. 21 The main obstacles in hydrogen storage are slow kinetics, poor reversibility, and high dehydrogenation temperatures for chemical hydrides.…”
Section: 3-11mentioning
confidence: 99%
“…Much work has focused on carbon-based materials such as nanotubes, [4][5][6][7][8][9][10][11][12][13][14] C 60 , 15,16 metal hydrides, and metal-organic frameworks, 17,18 titanium metallocarbohedryne, 19,20 and polyacethylene. 21 The main obstacles in hydrogen storage are slow kinetics, poor reversibility, and high dehydrogenation temperatures for chemical hydrides.…”
Section: 3-11mentioning
confidence: 99%
“…Interestingly, we found that even the dissociated structure can still absorb multiple H 2 , in which case, the system is somewhat similar to a Ti metallocarbohedryne ͑met-car͒ cluster. 27,28 …”
Section: Activation Energies and Reaction Paths Between Differentmentioning
confidence: 99%
“…6,7 Knowledge of the structures of metal-carbide clusters is important in understanding their potential applications. Despite this, many metal-carbide clusters still have unknown structures.…”
Section: Introductionmentioning
confidence: 99%